1977
DOI: 10.1084/jem.145.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent eosinophil-mediated damage to 51Cr-labeled schistosomula of Schistosoma mansoni: damage by purieid eosinophils.

Abstract: After earlier observations that antibody-dependent, cell-mediated damage to 51Cr-labeled schistosomula can be ablated by pretreatment of a mixed preparation of human peripheral blood leukocytes with an anti-eosinophil serum and complement, we investigated the cytotoxic effects of eosinophil-enriched cell preparations. Preparations containing up to 98.5% eosinophils and devoid of neutrophils were effective in mediating antibody-dependent damage to schistosomula. Preparations enriched in mononuclear cells or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(64 citation statements)
references
References 34 publications
4
60
0
Order By: Relevance
“…Furthermore, many helminths have developed elaborate mechanisms to evade host resistance, such as masking their surface or acquisition of host antigens (6). Recently several in vitro systems describing the interaction of the components of the host immune system and multicellular parasites have been developed to elucidate the mechanisms of resistance against these organisms (7)(8)(9)(10). Initially human eosinophils were demonstrated to damage the multicellular schistosomula of Schistosoma mansoni in the presence of specific anti-parasite antibodies (7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many helminths have developed elaborate mechanisms to evade host resistance, such as masking their surface or acquisition of host antigens (6). Recently several in vitro systems describing the interaction of the components of the host immune system and multicellular parasites have been developed to elucidate the mechanisms of resistance against these organisms (7)(8)(9)(10). Initially human eosinophils were demonstrated to damage the multicellular schistosomula of Schistosoma mansoni in the presence of specific anti-parasite antibodies (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that several immunoregulatory mechanisms may be operative in human schistosomiasis. The possible interference of IC with cellular defense mechanisms against S. mansoni has been suggested by others (Butterworth et al 1977, Kamal & Higashi 1982. Afterwards, studies on in vitro granuloma reaction have shown that IC obtained from sera of INT patients are able to suppress INT patients PBMC reactivity to PB-SEA and PB-SWAP (Goes et al 1991, Rezende et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not Eos emigration works for protection against or offers a comfortable environment for worms may be one of the important problems to be solved. Butterworth et al (1977) conceived that Eos had parasiticidal properties when working together with specific antibodies in experimental schistosomiasis in mice.…”
Section: Discussionmentioning
confidence: 99%